Unexpected Events in Practical Medicine or Ways to Provide Safety during Surgical Procedures - T. Toktomushev, Asanbek; K. Sayakov, Umetali; M. Ibraev, Bolot; D. Kerimov, Akilbek; U. Sayakova, Alia; A. Toktomusheva, Altinay (International Journal of Psychosocial Rehabilitation, 2020)
Clinical observations on unexpected events in practical medicine are rarely published in official scientific journals. However, this issue should be addressed seriously because certain tendencies and rational ideas can be revealed. Modern medicine relies on principles of standardization and clinical protocols of diagnostics and treatment that tend to exclude any untypical or unexpected events, which may ignore individual peculiarities of patients and methods of treatment. This provides a rationale for the present review. The presented information can be useful in practical medicine because in nonstandard or untypical situations, surgeons can make mistakes that lead to unpredictable consequences and threaten the patients’ safety. The aim of the study was to collect nonstandard events that occurred in practical medicine and to systematize them. Individual recommendations on handling such critical situations were provided. In surgical practice, surgeons face unexpected cases that not only surprise them but also require their concentration and attention in handling such situations. Unfortunately, sometimes, critical situations cannot be successfully handled and resolved. It may seem that causal events lie outside the scope of our understanding and cannot be explained rationally. However, everything can be explained rationally after certain considerations. The analysis of clinical observations allowed the authors to focus on the conflict situation "circumstances-patient-doctor-mistake.”. Materials and Methods. The review is based on 18 clinical observations. Results. Based on the clinical materials that contained information on untypical situations and events, the authors tried to systematize them by the cause. The authors provided recommendations on clinical medicine safety. Untypical situations were considered from the perspective of a patient’s safety. The authors discussed unprofessional approaches of doctors in such situations, issues of safety in clinical medicine and possible ways to handle such situations, legal issues in conflict situations, and ways to improve the safety in clinical medicine.